Aspiring regional power: Indonesian foreign policy under next president - Yang Razali Kassim (2016)
Whether it is Prabowo Subianto or Joko Widodo, Indonesia’s next president will have to deal with an increasingly assertive China. Tensions in the South China Sea will be his first major test.